A design method for half‐pipe jacketed vessels based on numerical limit‐load analysis. Issue 2 (9th February 2022) - Li, Weicong; Li, Huifang; Shi, Hong; Qian, Caifu
Abstract: As one kind of jacketed vessels, half‐pipe jacketed vessels are widely used in engineering owing to the structural and heat transfer advantages. But for the design of half‐pipe jacketed vessels, there are limitations in codes ASME VIII‐1 and ASME VIII‐2. In this paper, a new design method based on numerical limit‐load analysis is proposed to design half‐pipe jacketed vessels. The scheme and advantages of the method are presented through a design of half‐pipe jacketed vessel. It is found that by performing limit‐load analysis, problems of the codes ASME VIII‐1 and ASME VIII‐2 about the structural limitation of the half‐pipe jacketed vessels and loading limitation are solved. In addition, by performing limit‐load and parametric analysis, the strength weakness areas on the vessels can be found, and the rational strength design of a structure can be achieved.